Practical Steps of Shear Wave Elastography for Nonalcoholic Fatty Liver Disease in an Adult Population - Choorakuttil, Rijo Mathew; Chaubal, Rajas N.; Arunachalam, Venkatesh K.; Bagri, Neha; Gupta, Anjali; Bansal, Jitender; Pratap, Thara; Sodani, Varsha; Nirmalan, Praveen K. (Indographics, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a growing epidemic worldwide and is widely prevalent in India with a community-based study in South India reporting a prevalence of 49.8%. Imaging modalities are used to screen for NAFLD, identify different stages of the disease from early to advanced stages, and to monitor the progress of the condition and responsiveness to therapy. Computed tomography and magnetic resonance imaging modalities are used to assess NAFLD but have limitations in availability and affordability. B-mode ultrasound provides a viable imaging alternative but only provides a gross assessment and the presence or absence of fibrosis. Shear wave elastography is a newer modality that allows for the measurement of tissue stiffness or elasticity in response to tissue deforming forces generated as shear waves. The changes in elasticity can usually be determined before obvious structural changes and can be used for early diagnosis of disease and to assess the progress of the condition. In this article, we present the practical steps to perform an ultrasound shear wave elastography for the assessment and staging of NAFLD.
Keywords: elastography; nonalcoholic fatty liver disease; quality; shear wave; ultrasound